2021
DOI: 10.1088/1361-6587/abf85e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the toroidal flow and flow shear on the m/n = 2/1 tearing mode in J-TEXT tokamak

Abstract: The effect of the toroidal flow and flow shear on the m/n = 2/1 tearing mode (TM) has been investigated in J-TEXT tokamak, where m and n are the poloidal and toroidal mode numbers. It is found that the toroidal flow increment is linearly modulated by the bias current/return current. The frequency of the 2/1 TM is also found to be proportional to the toroidal flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The experimental result in DIII-D indicated that the increasing the flow shear could make the TM more stable by changing the equilibrium current profile [20]. However, electrode bias experiments have shown that the saturated island width of the TM is more correlated to the toroidal flow amplitude than the flow shear [21]. Hence, more experimental evidences are needed to identify the cause of the stabilizing effect on the TM.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result in DIII-D indicated that the increasing the flow shear could make the TM more stable by changing the equilibrium current profile [20]. However, electrode bias experiments have shown that the saturated island width of the TM is more correlated to the toroidal flow amplitude than the flow shear [21]. Hence, more experimental evidences are needed to identify the cause of the stabilizing effect on the TM.…”
Section: Introductionmentioning
confidence: 99%
“…As for the control of MHD instabilities, an active-control system is implemented in HBT-EP to control mode rotation with a biased electrode inserted into the plasma [21]. Previous experiments in J-TEXT have also demonstrated that bias can control the 2/1 tearing mode [22] and even unlock the locked mode [23]. In recent years, long-range correlation (LRC) structures have been observed in several devices during positive bias voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Toroidal rotation is thought to have a significant influence on MHD instabilities, including tearing modes and neoclassical tearing modes. It was observed that the tearing modes and neoclassical tearing modes were significantly affected by toroidal rotation in some experiments [2][3][4][5][6][7][8][9]. The mode amplitude of observed m/n = 2/1 tearing mode tended to be reduced by rotation and rotation shear in the Korea Superconducting Tokamak Advanced Research [10] (KSTAR) [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in ASDEX Upgrade, the onset threshold of neoclassical tearing modes was found to increase with co-and counter-current directed rotation, and also with positive and negative rotation gradient [7]. The effect of the toroidal flow and flow shear on the m/n = 2/1 tearing mode has been investigated in J-TEXT tokamak, which showed that the saturated island width of the tearing mode is more correlated to the toroidal flow amplitude than the flow shear [8].…”
Section: Introductionmentioning
confidence: 99%